Dissolution and precipitation behaviour in steels microalloyed with niobium during thermomechanical processing. (15th September 2015) - Gong, P.; Palmiere, E.J.; Rainforth, W.M.
Graphical abstract: Abstract: The thermomechanical processing of high strength low allow (HSLA) steels during low-temperature roughing, followed by rapid reheating to higher temperatures was investigated to better understand the Nb dissolution kinetics in austenite, and the subsequent precipitation behaviour during the final finishing passes. For comparative purposes, two experimental 0.06 wt% C steels were studied, one containing 0.03 wt% Nb (Nb steel), and the second containing both 0.03 wt% Nb and 0.02 wt% Ti (Nb–Ti steel). Processing of these steels consisted of a simulated roughing schedule, with the final roughing pass taking place at 850 °C. The strain-induced precipitation intensity in the steels subsequently quenched where characterised using transmission electron microscopy. Following this, the steels were rapidly reheated at a rate of 10 °C/s to a temperature of 1200 °C, held at temperature for various times, and water quenched to room temperature so that both the precipitate dissolution kinetics, together with the austenite grain coarsening kinetics could be established.